1997
DOI: 10.1093/glycob/7.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Purification of rabbit skeletal muscle proteoglycogen: studies on the glucosyltransferase activity of polysaccharide-free and -bound glycogenin

Abstract: Proteoglycogen is the end product in the process of glycogen biogenesis. We have purified rabbit muscle proteoglycogen and studied the glucosyltransferase reactions catalyzed by its protein moiety, glycogenin, free or bound to the polysaccharide. The purification strategy involved dissolution of proteoglycogen and cosedimenting membrane vesicles in a Triton X-114/Triton X-45 mixture followed by partition in the aqueous phase, potassium iodide precipitation of accompanying proteins, and washing by high-speed ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…14 C autoglucosylation was measured by precipitation, washing the labeled protein with trichloroacetic acid, and radioactivity counting as described (22). Unless indicated otherwise, the results represent the mean values of three independent experiments, and error bars show S.D.…”
Section: Methodsmentioning
confidence: 99%
“…14 C autoglucosylation was measured by precipitation, washing the labeled protein with trichloroacetic acid, and radioactivity counting as described (22). Unless indicated otherwise, the results represent the mean values of three independent experiments, and error bars show S.D.…”
Section: Methodsmentioning
confidence: 99%
“…Purified proteoglycogen was prepared from rabbit skeletal muscle as described previously (Carrizo et al, 1997). Briefly, the muscle was homogenized, the homogenate centrifuged at 4800 × g and proteoglycogen and membrane vesicles collected by centrifugation of the supernatant at 75,000 × g. The loose vesicles layer covering the proteoglycogen pellet was poured off, the pellet was dissolved in a 1.1% mixture of Triton X-114/Triton X-45 (86.5/13.5) at 4°C, and proteoglycogen was partitioned in the aqueous phase after raising the temperature of the solution to 14°C.…”
Section: Preparation Of Proteoglycogen C-glycogenin and Recombinantmentioning
confidence: 99%
“…We described a procedure for the isolation of native proteoglycogen from rabbit muscle and of polysaccharide-free glycogenin after exhaustive digestion of proteoglycogen with α-amylase (Carrizo et al, 1997). We also reported the release and isolation of C-chain-bound glycogenin (c-glycogenin) from isoamylolyzed muscle proteoglycogen; the c-glycogenin species was able to autoglucosylate, indicating that it was linked to a maltosaccharide capable of being elongated by autoglucosylation (Romero and Curtino, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Glycogenin can autoglucosylate and transglucosylate exogenous acceptors (5, 9 -11). Analysing the course of the simultaneous autoglucosylation of glycogenin and transglucosylation of dodecyl-␤-maltoside (DBM), we found that the transglucosylation reaction continued even when the acceptor capacity for autoglucosylation was exhausted (5). This result led us to consider the possibility that under the glycogen-bound form, the enzyme could transglucosylate DBM.…”
mentioning
confidence: 99%
“…Proteoglycogen and glycogenin. Proteoglycogen having polysaccharide-bound glycogenin as the only protein constituent was prepared from rabbit skeletal muscle as described previously (5). Glycogenin was released from proteoglycogen (150 g in glycogenin) by amylolysis with 3 g of ␣-amylase (purified as indicated before (12)) for 5 h at 25°C, in 1.0 ml of 3 mM Tris-acetate, pH 7.5, containing 0.06% sodium azide and 0.03 mM each of leupeptin, pepstatin and APMSF.…”
mentioning
confidence: 99%